2013
DOI: 10.1242/dev.081851
|View full text |Cite
|
Sign up to set email alerts
|

MEF2A regulates the Gtl2-Dio3 microRNA mega-cluster to modulate WNT signaling in skeletal muscle regeneration

Abstract: SUMMARYUnderstanding the molecular mechanisms of skeletal muscle regeneration is crucial to exploiting this pathway for use in tissue repair. Our data demonstrate that the MEF2A transcription factor plays an essential role in skeletal muscle regeneration in adult mice. Injured Mef2a knockout mice display widespread necrosis and impaired myofiber formation. MEF2A controls this process through its direct regulation of the largest known mammalian microRNA (miRNA) cluster, the Gtl2-Dio3 locus. A subset of the Gtl2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
126
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(138 citation statements)
references
References 57 publications
(68 reference statements)
5
126
2
Order By: Relevance
“…As previously reported by us and others, MEF2A depletion resulted in impaired myotube formation and differentiation (Fig. 2, A-C) (11,12). By contrast, individual depletion of the other MEF2 proteins failed to show any obvious impairment in myotube formation or differentiation (Fig.…”
Section: Mef2supporting
confidence: 84%
See 3 more Smart Citations
“…As previously reported by us and others, MEF2A depletion resulted in impaired myotube formation and differentiation (Fig. 2, A-C) (11,12). By contrast, individual depletion of the other MEF2 proteins failed to show any obvious impairment in myotube formation or differentiation (Fig.…”
Section: Mef2supporting
confidence: 84%
“…These shRNAs were designed to target all mRNA transcripts generated from each Mef2 gene. Previously, we described the specific and robust knockdown of MEF2A and MEF2C using shRNA adenoviruses (11,15). We subsequently generated shRNAs to specifically target MEF2B (Fig.…”
Section: Mef2mentioning
confidence: 99%
See 2 more Smart Citations
“…Knockout of the cluster, via knockout of the Meg3 locus, 17,18 led to overexpression of several proangiogenic genes, including Vegfa and Dll4, and drastically increased vascular capillary density in mouse embryos. 19 A recent study showed that the cluster is under transcriptional control of a binding site for the myocyte enhancer factor 2A (MEF2A), 20 a transcription factor known to influence vascular remodeling. 21,22 We show here that inhibition of individual 14q32 microRNAs leads to improvements in postischemic blood flow recovery in vivo.…”
mentioning
confidence: 99%